PERAN STAKEHOLDER DALAM PEMBERDAYAAN PETANI TEBU DI KABUPATEN DOMPU PROVINSI NTB - I Putu Cakra Putra Adnyana; Muhammad Saleh Mohktar (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
PT SMS, the central government in collaboration with the regional government of Dompu district in 2014 has developed sugarcane farming especially on dry land / moor accompanied by the construction of a sugar factory. The shift in the function of sugar cane development land is due to the conversion of technical irrigated rice fields into industrial buildings and other infrastructure. With the shift in sugarcane cultivation on dry land / moor it is expected to achieve national sugar self-sufficiency targets. The implementation of intensification and extensification of sugarcane farming on dry land can be done by assisting and escorting technology through the provision of appropriate technology (P3GI, 2008). The purpose of this study is 1). to find out the role of stakeholders in the activities of the Development of People's Sugar Cane in the concentrated sugar factory (PG) of PT SMS in Dompu Regency, 2). to find out the supporting and inhibiting factors of the role of stakeholders in the activities of the Development of People's Sugar Cane in PT SMS Dompu Regency. Based on the studies that have been conducted, it can be concluded that the relevant stakeholders in the Development of People's Sugar Cane in the work area of PT SMS have performed their roles well. This can be seen from the role of stakeholders in activities (1) Providing capital credit to sugarcane farmers; (2) Extension activities; (3) Partnership Meeting Forum Activities; (4) Core garden activities; and (5) payment system. It's just that extension workers in the plantation sector need to be improved by providing assistance to sugarcane farmers intensively.